Just as Surprised as Everybody Else: An Interview with Louise Welsh - Sánchez García, María Jesús (Complutense Journal of English Studies, 2025)
Applauded crime fiction author Louise Welsh published Plague Times, a cross-genre trilogy set in the context of a flu-like pandemic, only a few years prior to the outbreak of COVID-19. The fictional nature of Plague Times feels particularly realistic and ominous when read after enduring an actual global pandemic, due to Welsh’s thorough research on epidemics and her insight into human nature. This interview is articulated around how fiction and reality converged, and this understanding of human reactions in the face of fear. The subjects of solidarity—or lack thereof—and community are key as we approach the main characters, strangers who, following their own storyline in the first two instalments of the trilogy, finally team up in the last novel. Their journey is not only that of personal growth, but also geographical; there is a deliberate choice of locations contextualizing the development of both characters and story. This conversation takes place outdoors, on a sunny day in Louise Welsh’s Glasgow neighbourhood community garden, a coincidental parallelism with the optimistic outlook that permeates an otherwise sombre topic.